Potret Penggunaan Google Form Sebagai Media Evaluasi Pembelajaran SMA Al-Falah Bandung - ., Ahmad Fu’adin; ., Salsa Bila; ., Zahrani Putri Saidah; ., Zia Rahmawati Hidayat (CV. ITTC INDONESIA, 2023)
Since the Covid-19 pandemic, conventional learning evaluation media has shifted to digital to overcome various limitations at that time. Google Form is an alternative, namely a digital questionnaire to collect data more practically. Currently, the sustainability of using Google Form as one of the digital evaluation media after the pandemic in Indonesia has subsided has not been proven. Therefore, this article presents research on how the portrait of the use of Google Form at SMA Al-Falah Bandung by examining its advantages and disadvantages to be taken into consideration. This research uses a descriptive qualitative method by conducting interviews with teachers and distributing questionnaires to students. Our research shows that Google Form has advantages, namely varied forms of questions, simple features and appearance, flexible functions in learning, accelerating the management of evaluation results, ease to use, increasing technological capabilities, and realizing paperless trends. The disadvantages are the need for adequate devices, requiring a stable internet network, features and appearance that are no longer relevant to the needs of teachers.